Financial development in emerging countries: fintech, the new wave of development and the financial future (singapore as a model) - Nassour , Abdelkader; Larabi , Aicha (Journal of Research in Finance and Accounting, 2026)
Financial services have witnessed major changes in recent years, especially in the wake of the 2008 financial crisis, with regard to the growth of financial technology institutions and the trend of economies towards digital transformation with the slogan "Faster services, broader options with less cost". in this context, this paper aims to present the successful Singaporean model in adopting financial technology and achieving a qualitative leap in the development of the financial sector through a statistical study of the strategies and incentives provided to this sector. The results of the study showed that the government's prudent and ambitious monetary policy, as well as the great openness to the outside, short-term financial flows, and foreign direct investment, led to the dynamism of the real sector, and the development of the Singaporean financial sector. In turn, the strength and development of the financial industry has contributed to monetary stability and economic development in Singapore, where financial technology showed an important role in accelerating and diversifying financial services and reaching a wide segment of society.